Land dispute in the time of Kamakura through Ooyama Feudal literature - Phan, Hai Linh (Vietnam National University, Hanoi, 2020)
This report is focused on analyzing documents of the village Nishitai and introduces some preliminary comments on land disputes in Vietnam and Japan early time